Enhancing the Effectiveness of Public Spending Experience in OECD Countries - Joumard, Isabelle (OECD Economics Department Working Papers, 2004)
In most OECD countries, public spending rose steadily as a share of GDP over the past decades to the mid-1990s, but this trend has since abated. The spending pressures stemming from the continued expansion of social programmes have been partly compensated by transient or one-off factors. Pressures on public spending, however, appear likely to intensify, in particular as a consequence of ageing populations. Since most OECD economies have very little scope for raising taxation or debt to finance higher spending, reforms to curb the growth in public spending while raising its cost effectiveness are now required. This paper presents a reform strategy for progress in this direction, based on detailed country reviews for over twothirds of OECD countries. Three main areas for action are identified: the budget process; management practices and the use of market mechanisms in the delivery of public services ...